2010
DOI: 10.1139/v10-038
|View full text |Cite
|
Sign up to set email alerts
|

Serine–Ca2+versus serine–Cu2+complexes — A theoretical perspective

Abstract: The association of Ca 2+ and Cu 2+ to serine was investigated by means of B3LYP DFT calculations. The [serine-M] 2+ (M = Ca, Cu) potential energy surfaces include, as does the neutral serine, a large number of conformers, in which a drastic reorganization of the electron density of the serine moiety is observed. This leads to significant changes in the number and strength of the intramolecular hydrogen bonds existing in the neutral serine tautomers. In some cases, a proton is transferred from the carboxylic OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Also, in agreement with the behavior reported for serine, 25 the global minimum of the [Sec-Ca] 2+ PES is a CS structure, what is at variance with glycine, 46 where the global minimum of the PES is a SB structure. The interconversion between local minima of the [Sec-Ca] 2+ PES is reported in Figure 4.…”
Section: Conversely Complexes B(z) D(z)-f(z)supporting
confidence: 87%
“…Also, in agreement with the behavior reported for serine, 25 the global minimum of the [Sec-Ca] 2+ PES is a CS structure, what is at variance with glycine, 46 where the global minimum of the PES is a SB structure. The interconversion between local minima of the [Sec-Ca] 2+ PES is reported in Figure 4.…”
Section: Conversely Complexes B(z) D(z)-f(z)supporting
confidence: 87%
“…This situation changes significantly when glycine is replaced by serine or cysteine. For both aminoacids, the “conventional” CS structure in which the doubly charged metal ion interacts simultaneously with the carbonyl and the amino groups is again higher in energy than the SB‐type structure [72]. However, in these two cases the global minimum of the potential energy surface is another CS‐type structure ( c ), in which the metal dication appears tricoordinated by association not only with the carbonyl and the amino group, but also with the enol or enethiol group [72].…”
Section: Resultsmentioning
confidence: 99%
“…Du et al [15] reported that there is about 1 g/ml copper in human plasma, and the formation of Cu 2 + and amino acid complexes could promote the transport of copper to serum protein and participate in the metabolic and biochemical processes in human body. Researchers [16][17][18][19][20] have prepared a lot of research on the important role of amino acid metal complexes such as intramolecular proton migration of Cu 2 + with amino acid complexes has been studied. The result showed that the conformation of amphoteric alanine with the coordination of metal ions was the most stable.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the racemability of optically pure chiral amino acid metal complexes is very important for the health of life. The chiral transition of α-Ala Cu 2 + complex is also chiral while previous work [16][17][18][19][20] has only studied the proton transport reaction of the amino acid copper complex. Li et al [21] studied the chiral transition mechanism of the gas phase α-Ala ⋅ Cu 2 + complex, and the results showed that the racemization energy barrier of isolated α-Ala ⋅ Cu 2 + was about 120.0 kJ mol À 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation